A marginalização do princípio da autodeterminação dos povos: o Estado Islâmico (2004-2014) - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This paper analyzes the applicability of the principle of self-determination of peoples to the case of the Islamic State between 2004 and 2014 - years of more emphatic performance of the organization in the Levant region. In addition, it seeks to understand the structuring of the Contemporary International System, analyzing the formation of the Islamic State through war in a territory between two National States. To address the region's political and social history was impresfiable, from the emergence of Islam to the development of the Modern States in the Middle East, more specifically Syria and Iraq. Next, it deals with the development of International Law, a field that is related to International Relations, in order to understand the development of the organization of States, the formation of International Organizations and the emergence of self-determination of peoples in the system. Thereby, it becomes possible to understand the functional system of the system, which as subsidies, used the Kenneth Waltz Neorealist Theory and Alexander Wendt's Constructivist approach to understand the applicability of the principle of self-determination of peoples to the case of the Islamic State against a structure of states that does not corroborate with the emergence of new political and/or revolutionary organizations.
Keywords: Relações internacionais; Oriente Médio; Iraque; Síria; Autodeterminação dos povos; Estado Islâmico; Direito internacional; International relations; Self-determination; Islamic State; Middle East; Syria; Iraq; Sykes-Picot Agreement